2008
DOI: 10.1038/mi.2007.3
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with adenovirus at the large intestinal mucosa as an effective vaccination strategy against sexually transmitted viral infection

Abstract: The large intestinal mucosa contains immunological structures that may potentially serve as a site for induction of mucosal immunity against infections. Adenovirus (Ad), which is effective in gene transfer to epithelia, may be an ideal antigen delivery system for vaccination at the large intestinal mucosa. To investigate this potential, we immunized mice with recombinant replication-deficient Ad through a single intracolorectal (ICR) administration. Effective transfer of encoded genes was found in both the epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 75 publications
1
28
1
Order By: Relevance
“…However, our findings contrast with those of other studies that have suggested that mucosal rAd vector routing is advantageous for inducing CD8 ϩ T-lymphocyte responses at mucosal surfaces (14,16,27,32,36,43,46). We suspect that these differences may be related to the specifics of the various experimental systems utilized, such as differences in immunization techniques or vector doses.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our findings contrast with those of other studies that have suggested that mucosal rAd vector routing is advantageous for inducing CD8 ϩ T-lymphocyte responses at mucosal surfaces (14,16,27,32,36,43,46). We suspect that these differences may be related to the specifics of the various experimental systems utilized, such as differences in immunization techniques or vector doses.…”
Section: Discussioncontrasting
confidence: 99%
“…1A), whereas previous studies have shown that higher volumes of intranasal instillation mediate passage of the instillate to the lower respiratory tract (39). Some studies have also surgically or chemically manipulated mucosal surfaces (44,46), which could lead to persistent inflammation at the site of antigen delivery and alter the dynamics of antigen uptake and presen- Using adoptive transfer studies, we assessed the initial priming and trafficking patterns of antigen-specific CD8 ϩ T lymphocytes following immunization. I.m.…”
Section: Discussionmentioning
confidence: 99%
“…Small intestine was removed from mice and fragmented into small pieces and stirred for 30 min at 37°C with Ca 2ϩ -and Mg 2ϩ -free HBSS containing 10% FBS, 15 mM HEPES, 5 mM EDTA, 0.014% w/v DTT, and 100 g ml Ϫ1 gentamicin to isolate epithelial cells and IELs (10). IELs were purified from the cell suspension by a 40/67% gradient of Percoll (Sigma-Aldrich).…”
Section: Preparation Of Intraepithelial Lymphocytes (Iels) Of Small Imentioning
confidence: 99%
“…Most replication-defective viral vectors for genetic vaccination have been administered systemically and have successfully induced CD8 + T cell responses, but few of these vectors have been used for mucosal vaccination (31,32). HPV pseudoviruses (PsV), composed of the viral L1 and L2 proteins and a double-stranded DNA pseudogenome, have several attractive features as vectors for genetic immunization of the female genital mucosa, which is the natural target tissue for many HPV types.…”
Section: Introductionmentioning
confidence: 99%